Genomic composition and pathomechanisms of porcine circoviruses: A review - Yong-Yu Gao; Qian Wang; Han-Wen Li; Shuang Zhang; Jian Zhao; Di Bao; Han Zhao; Kai Wang; Gui-Xue Hu; Feng-Shan Gao (Virulence)
Porcine circovirus (PCV) belongs to the genus Circovirus within the family Circoviridae; it has the smallest genome and a complicated classification system comprising PCV1, PCV2, PCV3, and PCV4. Most types of these viruses can cause animals to develop serious diseases; in pigs in particular, it may manifest as postweaning multisystemic wasting syndrome (PMWS), reproductive failure, porcine dermatitis and nephropathy syndrome (PDNS), congenital tremors (CTs), proliferative and necrotizing pneumonia (PNP), lymphoid injury, and immunosuppression. Different types of PCVs cause different types of diseases and sometimes feature no pathogenicity; these various PCV types are associated with different pathomechanisms in animals. In this review, the genomic composition and systemic pathomechanisms of porcine circoviruses are introduced, and future research prospects are discussed.